An Interdisciplinary Team-Based Learning Experience in Ambulatory Patient Safety - Erik Black; Rick Davidson; Eric Rosenberg; Almut Winterstein; Ann Snyder; Wayne McCormack (Association of American Medical Colleges, 2013)
Abstract Introduction This interprofessional team-based learning experience in patient safety is intended to facilitate a review of barriers to health care quality in ambulatory care. Students from multiple health science professions prioritize shortcomings in health care delivery and discuss approaches to improve health care quality and public health while developing an appreciation for the complexity of health care delivery and impediments to quality health care. Methods This resource includes a facilitation guide, prereading assignments, an individual readiness examination, a team readiness examination, an application exercise case, and application exercise questions. The resource is implemented using the standard team-based learning format. Results In all, 622 learners from 10 separate degree programs across five colleges participated in this exercise. As expected, mean group performance was much higher than team performance; item metrics indicated that learners might not fully understand the difference between a medical error and an adverse event. Discussion This team-based learning experience was designed and implemented as a component of a required longitudinal interdisciplinary learning activity for first- and second-year students. Team-based learning was adopted as an instructional method based on its ability to promote discourse and involvement and to accommodate the limited number of faculty facilitators at our disposal.